Difenoconazole: A new seed dressing molecule for effective management of flag smut (Urocystis agropyri ) of wheat - Kumar, Sudheer; Kashyap, Prem Lal; Saharan, Mahender Singh; Singh, Ishwar; Jasrotia, Poonam; Singh, Devendra Pal; Singh, Gyanendra Pratap (Journal of Cereal Research, 2019)
Flag smut (FS) caused by Urocystis agropyri (Preuss) Schroet., is one of the major wheat yield limiting factors throughout the world. The chemical fungicides play a key role in effective and timely management of FS disease. To identify the suitable chemicals and appropriate dosages, five different fungicides Carboxin 17.5% + Thiram (17.5%), Tebuconazole (5.36%), Difenoconazole (3%), Flutriatol (25g L-1) and Carbendazim (50%WP) were evaluated at two different concentrations as seed treatment under field conditions in FS sick plots for two rabi seasons. The seed treatment withÂ Difenoconazole 3% (2.5 g kg-1 seed) provided complete protection (100%) against flag smut disease. Further, it was observed that the fungicide seed treatment not only controlled smut severity, but also avoided the yield losses and enhanced the wheat grain yield as compared to the control. Therefore, adoption of this fungicide as seed treatment to combat U. agropyri in absence of resistant cultivars in FS affected areas would benefit the farmers.